Adjunctive effect of systemic antimicrobials in periodontitis therapy: A systematic review and meta‐analysis. (27th July 2020) - Teughels, Wim; Feres, Magda; Oud, Valerie; Martín, Conchita; Matesanz, Paula; Herrera, David
Abstract: Aim: To answer the following PICOS questions: in patients with periodontitis, which is the efficacy of adjunctive systemic antimicrobials, in comparison with subgingival debridement plus a placebo, in terms of probing pocket depth (PPD) reduction, in randomized clinical trials with at least 6 months of follow‐up? Material and Methods: A systematic search was conducted: 34 articles (28 studies) were included. Data on clinical outcome variables changes were pooled and analysed using weighted mean differences (WMDs), 95% confidence intervals (CI) and prediction intervals (PIs), in case of significant heterogeneity. Results: For PPD, statistically significant benefits ( p < .001) were observed in short‐term studies (WMD = 0.448, 95% CI [0.324; 0.573], PI [−0.10 to 0.99]) and long‐term studies (WMD = 0.485, 95% CI [0.322; 0.648], PI [−0.11 to 1.08]). Additionally, statistically significant benefits were also found for clinical attachment level, bleeding on probing, pocket closure and frequency of residual pockets. The best outcomes were observed for the combination of amoxicillin plus metronidazole, followed by metronidazole alone and azithromycin. Adverse events were more frequently reported in groups using systemic antimicrobials. Conclusions: The adjunctive use of systemic antimicrobials in periodontal therapy results in statistically significant benefits in clinical outcomes, with more frequent adverse events in test groups using systemic antimicrobials.